Combined Effect of Abusive Supervision and Abusive Supervision Climate on Employee Creativity: A Moderated Mediation Model - Shen, Chuangang; Yang, Jing; Hu, Sanman (Frontiers in Psychology, 2020)
In accordance with social identity theory, a multi-level model is put forward to investigate how the “conjoint” associations between abusive supervision and abusive supervision climate exert influence on employee creativity through creative role identity. The data in this paper were from 357 supervisor-subordinate dyads in 77 working groups to test the proposed model. The results indicated that creative role identities mediated the relationship between abusive supervision and employee creativity, and group-level abusive supervision climate moderated the relationship between creativity and individual-level abusive supervision through the process of creative role identity, the mutual influence of abusive supervision climate and individual-level abusive supervision significantly predicated employee creativity. This paper also discusses related managerial and practical implications.